Effect of Incubation Time During Sperm Sexing Process on Sperm Quality of Pasundan Bull - Siti Darodjah Rasad; Nurcholidah Solihati; Kikin Winangun; Annisa Yusrina; Fahmy Avicenna (Indonesian Center for Animal Research and Development (ICARD), 2020)
The research was conducted to evaluate the effect of incubation time on viability, plasma membrane integrity, abnormality, and DNA integrity of sexed Pasundan’s bulls sperm. The sperm sexing used 5% and 10% concentrations of Bovine Serum Albumin (BSA). A completely randomized design with three treatments and six replications was used in this study. The data were analyzed using variance analysis followed by Duncan’s multiple distance test. Parameter evaluated were sperm longevity, plasma membrane integrity (PMI), abnormality, and DNA integrity of sexed Pasundan bulls sperm. Results showed that incubation time gave significant effect (P<0.05) on the longevity of sperm, but not on the PMI of Pasundan bulls sexed sperm. The incubation time of 45 minutes gave the highest value of longevity sperm on the upper layer (4.33 days) and the lower layer (4.17 days). Furthermore, the abnormality of sperm X in the upper layer was 4.00%-4.20% and the lower layer was 4.10%- 4.40%. Meanwhile, the DNA integrity of an upper layer was 98.16%-98.66%, and the lower layer was 97.83%-98.58%. It is concluded that 45 minutes of incubation time significantly affected the longevity of sperm, but not plasma membrane integrity, abnormality, and DNA integrity of Pasundan bulls sexed sperm.